Mountainous and forested hinterlands as a front line.Small peasants and petite gens in the work of Pierre Deffontaines - Antoine Huerta (Revue de Géographie Alpine)
This article aims to analyse Pierre Deffontaines' work on mountains and forests, focusing on small Mediterranean farmers, presenting them in a new light. As a field geographer, he had the opportunity to travel extensively through the Mediterranean mountains and study their rural populations. In addition to this personal taste, this small peasantry has an important place in his conception of geography, it forms the front of colonization ; it makes it possible to clarify a key concept of his geography : the small people (petites gens). This article deals with some unknown aspect of Deffontaines' productions where the study of these populations and the agropastoral forms associated with them is of great importance. This questions both the way Deffontaines thinks small farmers from a historical, geographical and ethnographic perspective. But also the place given to this author in the context of French geography of the classical period in a logic of historical and epistemological study. Pierre Deffontaines in 1948 developed a geography of transparency that left little room for problems. The Mediterranean example is particularly striking in his work because it supports the thesis of a pioneering function of the Mediterranean in the settlement and control of the land by humans. In his opinion, the origin of the world is then partly in the mountainous hinterlands and Mediterranean woodlands.